THE INFLUENCE OF THE STYLE OF THINKING AND THE IDEOLOGICAL SYSTEM OF THE SOCIETY ON THE SOCIAL DEVELOPMENT (Scientific journal of the Fergana State University, 2023)
The purpose of the study is to substantiate the mechanism of the influence of social ideology on the effectiveness of managing the social development of society. In the process of achieving this goal, the following tasks were solved: The essence of modern ideologies is studied. The importance of social ideology for managing the social development of society is substantiated. A mechanism for the influence of social ideology on the effectiveness of managing the social development of society has been formed. In this regard, it is important to conduct a special study to determine the nature of the influence of social ideology on the effectiveness of managing the social development of society. In the research process, methods of a non-linear, systematic approach of synergetics were used, as well as general scientific research methods, such as analysis, synthesis, logic, etc. The results of the study show that the effectiveness of managing the social development of a society depends on a number of factors, including social ideology, social culture, social activity of the state, social economy, strategic development of society, social system and coordination of interests of the state and society. The implementation of the solution allows creating the necessary conditions for the social development of society. This is fundamentally important, since social (economic and political) development in combination with global (domestic and foreign economic) development determines the correctness and quality of sustainable development, and the result is an increase in the standard of living of the population. In order to understand the logic of the influence of social ideology on the effectiveness of managing the social development of society, a study was conducted on the nature of the main modern ideologies developed in the 20th century. The results obtained led to the conclusion that social determinism, acting in conjunction with the ideologies of moral conservatism and economic dynamism, has a significant impact on the effectiveness of managing the social development of society.